2021
DOI: 10.1111/asap.12271
|View full text |Cite
|
Sign up to set email alerts
|

Does a report = support? A qualitative analysis of college sexual assault survivors’ Title IX Office knowledge, perceptions, and experiences

Abstract: Universities in the United States are required to remedy sexual assault under Title IX. Thus, college sexual assault survivors have the option to report to their university's Title IX Office as a mechanism for seeking sanctions and accommodations. The current study examined what survivors think about the Title IX Office, the possibility of seeking help there, and experiences with the reporting processes. Additionally, we examined the intersection between survivors’ gender and sexual identity in their perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 55 publications
4
17
0
Order By: Relevance
“…The findings from this study underscore both the importance and the perils of providing survivors options for recourse. For most of the participants in this study, the loss of control of their complaints was a source of harm, echoing previous research on institutional betrayal (Smith & Freyd, 2013, 2017) and survivors' negative experiences with Title IX reporting (Germain, 2016; Holland & Cipriano, 2021; Lorenz et al, 2022; Nesbitt & Carson, 2021). It follows that survivors need autonomy over the course of their complaints to feel truly supported by their universities.…”
Section: Discussionsupporting
confidence: 81%
“…The findings from this study underscore both the importance and the perils of providing survivors options for recourse. For most of the participants in this study, the loss of control of their complaints was a source of harm, echoing previous research on institutional betrayal (Smith & Freyd, 2013, 2017) and survivors' negative experiences with Title IX reporting (Germain, 2016; Holland & Cipriano, 2021; Lorenz et al, 2022; Nesbitt & Carson, 2021). It follows that survivors need autonomy over the course of their complaints to feel truly supported by their universities.…”
Section: Discussionsupporting
confidence: 81%
“…Some of what participants described represented Title IX staff prioritizing due process and neutrality over care for survivors, consistent with prior research on Title IX Coordinators (Cruz, 2021). Student descriptions of the confusing, opaque, and harmful aspects of the Title IX process reinforce findings from prior research (e.g., Fleming et al, 2021; Germain, 2016; Holland & Cipriano, 2021; Holland & Cortina, 2017; Khan et al, 2018; Nesbitt & Carson, 2021; Sall & Littleton, 2022). These experiences contributed to a perception of the Title IX process as overwhelmingly negative, unhelpful, and untrustworthy, and for many students enacted a sense of institutional betrayal (i.e., a perception that their institutions would not protect or support them).…”
Section: Discussionsupporting
confidence: 68%
“…Institutional betrayal was especially relevant for non-binary students, women students, Black students, and students with disabilities, who described ways in which they were disserved by the Title IX process and how this may have negatively impacted the outcome of their cases. This echoes Holland and Cipriano (2021), who found that only cisgender women (not transgender women, non-binary individuals, or cisgender men) in their sample reported to the Title IX office, and it was only two White women whose perpetrators were found “responsible.” Similarly, Sall and Littleton (2022) found higher rates of institutional betrayal endorsed among racial/ethnic minority women compared to White women.…”
Section: Discussionmentioning
confidence: 58%
“…At MSU, our harms were large-scale, catastrophic, and very public, and many IHEs have policies and practices that disregard the needs of or are harmful to survivors. IHEs harm survivors when they disempower their choices and control (Holland et al, 2018), when they make help-seeking burdensome and retraumatizing (Holland & Cipriano, 2021), and when they do not even offer help to marginalized and minoritized communities (Jacobson López, 2023). IHEs must take meaningful action to stop these abuses.…”
Section: Discussionmentioning
confidence: 99%